New Clinical and Laboratory Findings of SHAPU - Manandhar, Anu; Margolis, Todd P; Khanal, Bhaiya (Nepalese Journal of Ophthalmology, 2018)
Introduction: The cause of Seasonal hyperacute panuveitis (SHAPU) also known as seasonal endophthalmitis is not yet confirmed. So far, bacteria have been isolated from the vitreous of three cases, VZV from the aqueous of one case and anellovirus from the vitreous of 30 cases of SHAPU. Its connection with moth is still assumed but not proven yet. Objective: To study the clinical and microbiological features of SHAPU. To find out indirect evidence of it connection with moths. Method: Prospective longitudinal study of all the cases of SHAPU observed at Tilganga Institute of Ophthalmology in 2009 and 2010. A detailed ocular examination was performed on each case and vitreous fluid was removed from almost all cases for microbiological study. Result: 66 cases of SHAPU were identified. Most were children. Twenty-three percent reported a recent history of white moth contact. Fine brown hairs, were present in 5 eyes. Bacteria were isolated from the vitreous of 9 eyes, PCR testing of the vitreous of all 48 cases showed no evidence of HSV, VZV or CMV DNA. Twenty of 34 cases (58.8%) who presented within 7 days of onset of symptoms had a final visual acuity ≥ 6/60 whereas 4/25 cases (16.0%) who presented after 7 days had final visual acuity ≥ 6/60 (p=0.001). Conclusion: Herpes group of virus is the less likely cause of SHAPU. Bacteria are found in more cases. Early presentation is associated with a better visual outcome. Role of moth in its pathogenesis is still suspected.